A Rare Cause of Angina After Coronary Bypass Grafting; Left İnternal Mammary Artery to Pulmonary Artery Fistula and Successful Treatment with Transcatheter Coil Embolization - Calik,Ali Nazmi (2019)
Abstract Fistula from left internal mammary artery (LIMA) to pulmonary artery (PA) is rarely encountered in daily practice. In recent years, endovascular therapy options have emerged for the treatment of fistula formations and replaced with surgery. A 53-year-old man admitted to our outpatient clinic with symptoms of typical angina and shortness of breath despite optimal medical therapy. In his relevant history, he had a coronary artery bypass graft (CABG) operation in 2009 in which his LIMA was anastomosed to left anterior descending (LAD) and ramus artery sequentially. Coronary angiography including selective imaging of LIMA demonstrated a fistula formation originating from the proximal portion of the LIMA and draining to PA. After successful closure of fistula with transcatheter coil embolization, the patient was discharged without any complication and symptom. In conclusion, although LIMA to PA fistula is an infrequent clinical condition, it should be considered as a potential cause of persistent angina after CABG operation. Treatment options include conservative medical therapy, surgical ligation and endovascular interventions. The best therapy should be individualised for each patient in respect to patient’s symptoms, surgical compatibility and anatomy of fistula.